159 - DEFRAUD AND IMAGE RIGHT OF THE PROFESSIONAL FOOTBALL PLAYER (Fiep Bulletin - online, 2011)
Firstly, this paper analyzes the professional football player and his conception as an employee and liable to labor rights. It not only exposes a brief history of the development of the legal relationships between the football player and the sports practice association, but also relates the amount of money which is called "the right of arena" and "image rights". Finally, it describes the possibility of using the image right in order to defraud the employment relations by creating a legal entity on behalf of the athlete.
Keywords: professional athlete; right image; fraud